Logistics Management Information System (LMIS) for Health Commodities at Public Health Facilities in Amhara National Regional State of Ethiopia: A Data Quality Evaluation Survey [Response to Letter] - Mekonen ZT; Cho DJ; Fenta TG (Journal of Multidisciplinary Healthcare)
Zelalem Tilahun Mekonen,1 Denny J Cho,2 Teferi Gedif Fenta1 1Department of Social and Administrative Pharmacy, Addis Ababa University, Addis Ababa, Ethiopia; 2Logistics Department, Kyrgyz State Technical University, Bishkek, KyrgyzstanCorrespondence: Zelalem Tilahun Mekonen, Email zelalem.tilahun@aau.edu.et